Implementing Problem-Based Learning to Enhance Students' Mathematical Proficiency in Primary School - Ujiati Cahayaningsih; Mohamad Gilar Jatisunda; Dede Trie Kurniawan; Dede Salim Nahdi; Wulan Putri Utami; Rahma Halipah (Didaktik Matematika, 2023)
Primary school students' mathematical proficiency is crucial to their academic progress. However, many students still struggle to understand math, especially fractions. This study examines how Problem-Based Learning (PBL) improves primary school students' mathematical proficiency. The study employed a quasi-experimental approach to investigate the effects of PBL academic achievement. The experimental group received PBL, while the control group received expository teaching. This study selected 54 students from two primary schools using purposive sampling. The experimental group consisted of 28 students, and the control group had 26. Students' mathematical proficiency was tested pre-and post-intervention.The findings reveal a significant improvement in mathematical proficiency in the experimental class exposed to PBL, as indicated by the independent samples t-test. The two-way ANOVA underscores the interaction influence of PBL and Early Mathematics Skills (EMS) factor on improving mathematical proficiency, supported by a high R-squared value (0.941). It suggests that PBL explains a substantial portion of the observed diversity in mathematical proficiency. The quasi-experimental approach has limitations, and the study shows that PBL improves mathematical proficiency. The study's quasi-experimental characteristics and potential lack of generalizability are acknowledged. While recognizing students' starting EMS, educators and policymakers should incorporate PBL into mathematics instruction, especially for complex concepts like fractions